Development Module of Global Warming Issue to Train Science, Technology, Engineering, and Mathematics (STEM) Literacy - Febrina Aspyan Tari; Irma Rahma Suwarma; Lilik Hasanah (Journal of Innovative Science Education, 2023)
Teaching materials can improve students' skills. Global warming material is important to learn to solve social problems or global issues. Therefore, this study aims to develop an integrated STEM module on global warming material to train learners' STEM literacy. This research method is Research and Development (R&D). The data is analyzed descriptively. N-gain is used to determine module effectiveness and improve students' STEM literacy. The sample in this study was class X which amounted to 36 learners. The results showed that the STEM-based modules developed had criteria suitable for use in the learning process in terms of suitability of the material with STEM with a validation score of 0.75 in the high category (feasible), and aspects of the feasibility of teaching materials which were divided into several assessments with a score of 0.87 in the very high category (very feasible), module design with a score of 0.86 in the very high category (very feasible) and the language component with a score of 0.85 in the very high category (very feasible), The average perception of learners towards the use of modules in the overall learning process is 70.53 medium categories. STEM-based modules are suitable to be used as an alternative source of learning global warming in physics learning to train students' STEM literacy.